The Soluble N-Ethylmaleimide-Sensitive Factor Attached Protein Receptor Complex in Growth Cones: Molecular Aspects of the Axon Terminal Development - Igarashi, Michihiro (J Neurosci, 1997)
Soluble N-ethylmaleimide-sensitive factor attached protein (SNAP) receptor (SNARE) mechanisms are thought to be involved in two important processes in axonal growth cones: (1) membrane expansion for axonal growth and (2) vesicular membrane fusion for mature synaptic transmission. We investigated the localization and interactions among the proteins involved in SNARE complex formation in isolated growth cone particles (GCP) from forebrain. We demonstrated that the SNARE complex is present in GCPs morphologically without synaptic vesicles (SVs) and associated with growth cone vesicles. However, the apparently SV-free GCP was lacking in the regulatory mechanisms inhibiting SNARE complex formation proposed in SV fusion, i.e., the association of synaptotagmin with the SNARE complex, and vesicle-associated membrane protein (VAMP)-synaptophysin complex formation. The core components of the SNARE complex (syntaxin, SNAP-25, and VAMP) accumulated for several days before postnatal day 7, when SVs first appeared, and preceded the accumulation of marker proteins such as synaptophysin, SV2, and V-ATPase. Our present results suggest that the SNARE mechanism for vesicular transmitter release is not fully functional in growth cones before the appearance of SVs, but the SNARE mechanism is working for membrane expansion in growth cones, which supports our recent report. We concluded that the regulation of the SNARE complex in growth cones is different from that in mature presynaptic terminals and that this switching may be one of the key steps in development from the growth cone to the presynaptic terminal.